Media Pembelajaran Ular Tangga dalam Meningkatkan Kosakata Bahasa Jerman - Ludgardis Ludgardis; Burhanuddin Burhanuddin; Misnawaty Usman (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. The purpose of this study was to obtain data and information about the effectiveness of Snakes and Ladders learning media in increasing the German vocabulary of class XI students of SMA Negeri 2 Komodo. This type of research is an experimental quantitative research model using a Pre-Experimental design in the form of One Group Pretest-Posttest Design. The population of this research is the students of class XI SMA Negeri 2 Komodo. The sample is 1 class, namely class XI Language and Culture which consists of 30 students. The sample of this study was selected using a total sampling technique. The data were collected using a test, while the research data were analyzed descriptively and inferentially with the t-test. The results of data analysis showed that the value of tcount was 79.31 ttable 2.002 at a significant level of 0.05. The results of this study indicate that Snakes and Ladders learning media in improving German Vocabulary of class XI students of SMA Negeri 2 Komodo is effective. Keywords: Effectiveness, Snakes and Ladders Media, German Vocabulary